2021
DOI: 10.3390/molecules26175142
|View full text |Cite
|
Sign up to set email alerts
|

Coumarins as Tool Compounds to Aid the Discovery of Selective Function Modulators of Steroid Hormone Binding Proteins

Abstract: Steroid hormones play an essential role in a wide variety of actions in the body, such as in metabolism, inflammation, initiating and maintaining sexual differentiation and reproduction, immune functions, and stress response. Androgen, aromatase, and sulfatase pathway enzymes and nuclear receptors are responsible for steroid biosynthesis and sensing steroid hormones. Changes in steroid homeostasis are associated with many endocrine diseases. Thus, the discovery and development of novel drug candidates require … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…It has been shown that 3-phenylcoumarins (31-35) (G. Luo et al, 2017;Guoshun Luo et al, 2017;S. Niinivehmas & Pentikäinen, 2021) are able to suppress BC by blocking specific hormonal enzymes like hormonal estrogen receptor-α (ER-α) as it can mimic steroid compound binding in ER and thus offer a solution to affect ER activity (Kumar, Sunita, Jha, & Pattanayak, 2018;S.…”
Section: Coumarins In Breast Cancermentioning
confidence: 99%
“…It has been shown that 3-phenylcoumarins (31-35) (G. Luo et al, 2017;Guoshun Luo et al, 2017;S. Niinivehmas & Pentikäinen, 2021) are able to suppress BC by blocking specific hormonal enzymes like hormonal estrogen receptor-α (ER-α) as it can mimic steroid compound binding in ER and thus offer a solution to affect ER activity (Kumar, Sunita, Jha, & Pattanayak, 2018;S.…”
Section: Coumarins In Breast Cancermentioning
confidence: 99%
“…Coumarin derivatives readily interact with a variety of enzymes and receptors in breast cancer cells. Moreover, the coumarin-based irosustat drug is known to interact with sulfatase enzyme, indicating that coumarin derivatives are potential materials for anti-breast cancer agents [20]. In the last 30 years, doctors have made great strides in early diagnosis and treatment of the disease and in reducing breast cancer deaths.…”
Section: Introductionmentioning
confidence: 99%